Cisplatin-Induced Downregulation of OCTN2 Affects Carnitine Wasting - Lancaster, C.; Hu, C.; Franke, R.; Filipski, K.; Orwick, S.; Zhaoyuan, C.; Zuo, Zhili; Loos, W.; Sparreboom, A. (American Association Cancer Research, 2010)
Purpose: Carnitine is an essential cofactor for mitochondrial fatty acid oxidation that is actively reabsorbed by the luminal transporter Octn2 (Slc22a5). Because the nephrotoxic agent cisplatin causes urinary loss of carnitine in humans, we hypothesized that cisplatin may affect Octn2 function. Experimental Design: Excretion of carnitine and acetylcarnitine was measured in urine collected from mice with or without cisplatin administration. The transport of carnitine was assessed in cells that were transfected with OCT1 or OCT2. The effect of cisplatin treatment on gene expression was analyzed using a mouse GeneChip array and validated using quantitative reverse transcriptase-PCR.Results: In wild-type mice, urinary carnitine excretion at baseline was ∼3-fold higher than in mice lacking the basolateral cisplatin transporters Oct1 and Oct2 [Oct1/2(−/−) mice], indicating that carnitine itself undergoes basolateral uptake into the kidney. Transport of carnitine by OCT2, but not OCT1, was confirmed in transfected cells. We also found that cisplatin caused an increase in the urinary excretion of carnitine and acetylcarnitine in wild-type mice but not in Oct1/2(−/−) mice, suggesting that tubular transport of cisplatin is a prerequisite for this phenomenon. Cisplatin did not directly inhibit the transport of carnitine by Octn2 but downregulated multiple target genes of the transcription factor peroxisome proliferator activated receptor α, including Slc22a5, in the kidney of wild-type mice that were absent in Oct1/2(−/−) mice. Conclusion: Our study shows a pivotal role of Oct1 and Oct2 in cisplatin-related disturbances in carnitine homeostasis. We postulate that this phenomenon is triggered by deactivation of peroxisome proliferator activated receptor α and leads to deregulation of carnitine-shuttle genes.